Pola Asuh Orang Tua dan Tingkat Kemandirian Pemenuhan Kebutuhan ADL (Activity of Daily Living) pada Anak Tunagrahita: Parenting Patterns and the Level of Independence in Fulfilling ADL (Activity of Daily Living) Needs in Mentally Disabled Children - Yesi Permatasari; Wesley Daely; Yeni Koto (Journal of Nursing Education and Practice, 2023)
Introduction: Mentally retarded children have limitations in taking care of themselves due to their motor and cognitive factors. The role of parents is very important to improve the ability of disabled children to be independent in fulfilling the needs of daily activities such as eating, toileting, and dressing. There are three types of parenting, authoritarian, permissive, and democratic. Objectives: This study aims to determine whether or not there is a relationship between parenting parents and the level of independence in fulfilling ADL in children with disabilities. Method: The method used in this research is quantitative descriptive analysis, the sample size is 35 parents who have mentally retarded children at SLB Mekar Sari 1 Cibinong using a total sampling technique, collecting data using a questionnaire. Result: After the Chi-Square test was carried out, a p-value of 0.007 was obtained so that the p-value <0.05. Conclusion: This study has limitations in self-care due to a motor and cognitive factors. So it can be concluded that there is a relationship between parenting style and the level of ADL independence of children with disabilities at SLB Mekar Sari 1 Cibinong.